Dampak Tegangan Induksi Petir pada Tangki Penyimpanan Bahan Bakar Cair Flammable - utama, Budi (ReTII, 2019)
ABSTRACT This paper analyses the induced voltage of the lightning that accumulated into the body of the fuel tank structure, moment after a lightning stroke hit the rod of lightning protection at the top of its protection tower. The protection mast and the lightning rod are 33 m and 6 m in heigh respectively. The Calculation of the induced voltage were simulated and carried out using Matlab software for finding the shape impulse wave and magnitude of the inducing voltage of the lightning that were accumulated in the tank structure. This analysis depicts that the lightning induction voltage varies with the distance between the lightning rod position and tank location, so that any changes in the induced voltage value are followed by changes the limitation of the minimum air gap in the tank.The results are very important to know the parameters that causes a fire and an incendive spark in the tank.